2009
DOI: 10.1128/jcm.01592-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phenotypic Tests for Detection of Metallo-β-Lactamase-Producing Pseudomonas aeruginosa Strains in China

Abstract: A total of 264 nonduplicate strains of imipenem (IPM)-nonsusceptible Pseudomonas aeruginosawere isolated from hospitals in 16 different regions throughout China. These 264 IPM-nonsusceptible clinical isolates of P. aeruginosa were examined by PCR, a metallo-␤-lactamase (MBL) Etest, a double-disk synergy test (DDST), and a test using combined IPM disks supplemented with various amounts of EDTA. A total of 24 strains positive for MBLs were confirmed by PCR and DNA sequence analysis: 10 strains positive for the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 27 publications
5
42
1
2
Order By: Relevance
“…[33] In the current study, IPM-EDTA DDST showed a medium degree of agreement with PCR assay 37.5% sensitivity and 100% specificity. This finding agreed with studies performed by [34,9] . However, the result of the sensitivity may have increased if the distance between the inhibitor and the substrate was 15 mm instead of 20mm as reported by.…”
Section: Discussionsupporting
confidence: 93%
“…[33] In the current study, IPM-EDTA DDST showed a medium degree of agreement with PCR assay 37.5% sensitivity and 100% specificity. This finding agreed with studies performed by [34,9] . However, the result of the sensitivity may have increased if the distance between the inhibitor and the substrate was 15 mm instead of 20mm as reported by.…”
Section: Discussionsupporting
confidence: 93%
“…Double-disk synergy tests (DDS) [17] and combined disk (CD) assays [18] were performed to screen MBLs producers. An increased zone diameter of ≥ 6 mm around the disk containing imipenem supplemented with EDTA compared to the disk containing imipenem alone was interpreted as MBLs production.…”
Section: Detection Of Mbl Producers By Phenotypic Methodsmentioning
confidence: 99%
“…Modified Hodge test detects only carbapenemase activity, which prevents the use of EDTA and therefore, does not confirm the metal dependence of the carbapenemase (Kali et al, 2013). Modified Hodge test, DDST and the CDT are easy, reliable, simple to perform and cheaper (Qu et al, 2009). The CDT is the most sensitive techniques for detecting MBL compared to DDST (Biradar and Roopa, 2015).…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%